Perancangan Media Poster Sebagai Sarana Promosi dan Informasi pada Website Kopi Es Tak Kie Menggunakan Metode Design Thinking - Ade Lia Kurnia Safitri; Ahmad Fuad (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
Posters are an important means of conveying information and promoting products or services to a wider audience through the power of visual communication. This research focuses on redesigning promotional and informational posters to support the marketing strategy of the Kopi Es Tak Kie website, a long-standing Chinese culinary heritage in Jakarta. The main objectives of this research are to enhance visual appeal, expand market reach, and strengthen cultural values ​​through print media designs that are representative and relevant to the development of the digital era. The approach used is visual communication design with the Design Thinking method. The stages in this method include audience needs research, design concept design, prototyping, and usability evaluation involving target respondents. In the visualization process, Figma software was used to arrange the poster layout, while Procreate was utilized to create complementary illustrations that provide an artistic and authentic feel. The resulting poster design emphasizes the use of a color palette of brick red, cream, and dark blue, combined with script and sans-serif typography. This combination was chosen to convey a cultural message while emphasizing the exclusive image of the Kopi Es Tak Kie brand. The visual harmony of color and typography enhances the cultural narrative while emphasizing the modern brand identity. The primary audience for this poster is young adults aged 22–40 who are interested in the fusion of traditional coffee culture and modern lifestyle. The findings of this study indicate that the redesigned poster is effective in bridging cultural heritage with digital branding, strengthening the identity of Kopi Es Tak Kie across both offline and online platforms. Thus, the poster medium is proven to act as a communication bridge connecting historical values ​​with contemporary marketing strategies.